"I would love to be 'discredited' like this more often": An interview with Irving Kirsch. Issue 3 (2nd January 2023) - Cardeña, Etzel
ABSTRACT: This interview with Professor Irving Kirsch took place in late August, 2022. He recently turned 80 years old and agreed to focus his interview on topics and areas that illustrate his influence on the field of hypnosis. Professor Kirsch discusses the influences that shaped him as a person and scientist; what unites his theoretical and research work on hypnosis, placebo, and antidepressants. He also addresses the importance of response expectancies, why clinicians should learn hypnosis and what he considers the source of his greatest personal and professional fulfillments.